MiR‐124‐3p improves mitochondrial function of renal tubular epithelial cells in db/db mice. Issue 3 (8th February 2023) - Liang, Luqun; Wo, Chunxin; Yuan, Yao; Cao, Hongjuan; Tan, Wanlin; Zhou, Xingcheng; Wang, Dan; Chen, Rongyu; Shi, Mingjun; Zhang, Fan; Xiao, Ying; Liu, Lingling; et al.
Abstract: Diabetic kidney disease (DKD) is one of the most serious complications of diabetes mellitus (DM) and the main cause of end‐stage renal failure. However, the pathogenesis of DKD is complicated. In this study, we found that miR‐124‐3p plays a key role in regulating renal mitochondrial function and explored its possible mechanism in DKD progression by performing a series of in vitro and in vivo experiments . Decreased expression of miR‐124‐3p was found in db/db mice compared to db/m mice. Moreover, miR‐124‐3p down‐regulated FOXQ1 by targeting FOXQ1 mRNA 3′‐UTR in NRK‐52E cells. Also, an increase in FOXQ1 and down‐regulation of Sirt4 were found in db/db mouse kidney and renal tubular epithelial cells cultured with high glucose and high lipid. Overexpression of FOXQ1 could further down‐regulate the expression of Sirt4 and aggravate the damage of mitochondria. Conversely, the knockdown of the FOXQ1 gene induced Sirt4 expression and partially restored mitochondrial function. To verify the effects of miR‐124‐3p on Sirt4 and mitochondria, we found that miR‐124‐3p mimics could up‐regulate Sirt4 and inhibit ROS production and MitoSOX, thus restoring the number and morphology of mitochondria. These results showed that under high‐glucose and high‐lipid conditions, the down‐regulation of miR‐124‐3p induces FOXQ1 in renal tubular epithelial cells, which in turn suppresses Sirt4 and leads to mitochondrial dysfunction, promoting the development of DKD. Abstract : The schematic illustrates that down‐regulation of miR‐124‐3p induces FOXQ1, which in turn suppresses Sirt4 and leads to mitochondrial dysfunction, promoting the development of DKD. FOXQ1: fork‐head transcription factor Q1. Sirt4: sirtuin4. ROS: reactive oxygen species. MitoSOX: mitochondrial superoxide. ECM: extracellular matrix. DKD: diabetic kidney disease.